FACTORS DETERMINING STUDENTS’ IN CHOOSING ACCOUNTING DIPLOMA AS A MAJOR - Cempaka, Adisti Gilang (Jurnal Ekonomi dan Bisnis Terapan, 2018)
The study investigates factors determining students’ choice of accounting major. The sample was collected from a survey of student in four-years vocational studies (D-IV Tax Accounting) Faculty of Economics and Business Universitas Padjadjaran. The study results show factors affect students’ major decisions are numerous but they can be group into personal, reference and job factors. The findings indicate that personal and job factors such as students’ believe that learning accounting is challenging, willingness to learn accounting, motivation in the subject, high availability job, high market demand of an accountant, flexibility in career choice, are the most considerable factors of students’ choice in accounting. The study also shows significant differences between female and male student. In particular, female students were found to be more influenced by the reference factors than their male counterparts in the choice of accounting.